Evaluación de proyectos con opciones reales: aplicación a un proyecto inmobiliarío con punto de equilibrio - Guevara Guevara, Paola (2009)
This paper applies a business and investment project valuation model that integrates Discounted Cash Flow and Real Options Analysis, showing that the results of our investments may vary depending on the flexibility that managers have in decision making within projects. This integrated approach is a way of determining the value of flexibility in future activities. The project involves the construction of a condominium in an area of 300m2 located in the area of Portón the Lomas, in the city of Guayaquil. This consists of 10 departments distributed on a ground floor and 4 floors; each apartment has parking lots that are located in the basement and in front of the condominium; will feature first-class finishes. As access to each floor, there will exist an elevator in addition to the stairs. This project is analyzed under two business models: the first involving the construction of the condominium and, then, the selling of the departments; and the second one, which includes a EN PLANOS selling of the departments y then the construction of the building only if a good selling was accomplished. The result of the valuation of our project in the first model indicates that business is profitable but low profits are expected to generate a Net Present Value of $ 2,079.40. The second business model, which contains a pre-stage, can be considered as a project with a “delay option” that provides flexibility as it enables decision making that minimizes the risk to investors. It was determined that this step amounted to a expected Present Value of $ $36,624.44;.therefore demonstrating that the delay option has a value of $34,545.04 and can mitigate the risk we face when doing a project.